2015
DOI: 10.7314/apjcp.2015.16.9.3917
|View full text |Cite
|
Sign up to set email alerts
|

Dendrosomal Curcumin Suppresses Metastatic Breast Cancer in Mice by Changing M1/M2 Macrophage Balance in the Tumor Microenvironment

Abstract: Curcumin, a lipid-soluble compound extracted from the plant Curcuma Longa, has been found to exert immunomodulatory effects via macrophages. However, most studies focus on the low bioavailability issue of curcumin by nano and microparticles, and thus the role of macrophages in the anticancer mechanism of curcumin has received little attention so far. We have previously shown the potential biocompatibility, biodegradability and anti-cancer effects of dendrosomal curcumin (DNC). In this study, twenty-seven BALB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 47 publications
(49 reference statements)
3
45
1
1
Order By: Relevance
“…47 We also examined the effect of CUR against tumor growth in vivo , and we found that it significantly reduced the tumor size. Our findings are in agreement with previous studies which reported the ability of CUR to reduce tumor size in human 41,48 or mice 23,49 breast cancer cells. Although <1% of oral CUR actually enter the plasma, 50 most studies depend on oral administration of CUR to treat different diseases.…”
Section: Discussionsupporting
confidence: 94%
“…47 We also examined the effect of CUR against tumor growth in vivo , and we found that it significantly reduced the tumor size. Our findings are in agreement with previous studies which reported the ability of CUR to reduce tumor size in human 41,48 or mice 23,49 breast cancer cells. Although <1% of oral CUR actually enter the plasma, 50 most studies depend on oral administration of CUR to treat different diseases.…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, curcumin moderates the accumulation of MDSCs and MDSC‐mediated IL‐6 secretion in tumors, leading to an inhibition of gastric cancer xenograft tumor growth . In agreement with these results, curcumin suppresses metastatic breast cancer in mice by increasing M1 and decreasing M2 macrophage populations in the TME, resulting in decreased STAT3, IL‐10, and arginase I gene expression and secretion . Another study revealed that curcumin nanoparticles upregulate the expression of the costimulatory molecule CD86 in DCs and decrease the secretion of proinflammatory cytokines (IL‐1β, IL‐6, IL‐8, IL‐10, and tumor necrosis factor α [TNF‐α]) from activated T cells, leading to their enhanced cytolytic ability against esophageal adenocarcinoma cells .…”
Section: Natural Compounds Possessing Epigenetic Properties That Stimsupporting
confidence: 56%
“…Additionally, some CC‐CD68Ab molecules that are targeted to and taken up by GBM‐associated microglia would be expected to stimulate these cells to release cytokines to kill the GBM cells and then eliminate the dead cells through phagocytosis. However, this would require CC‐mediated alteration of the tumor‐associated microglia population from the tumor‐promoting M2 to the tumoricidal M1 state …”
Section: Discussionmentioning
confidence: 99%
“…Thus it is likely that plant‐derived foods play an important role in stimulating our immune system to eliminate cancer cells. Curcumin regulates the activity of T‐cells in the peripheral immune system and also the macrophages . Although the brain is not expected to harbor the complete battery of lymphocytes and the complement system of the peripheral tissue, it has been shown to harbor microglia, which in their pro‐inflammatory M1 state serve as antigen‐presenting immune cells that are known to kill cancer cells .…”
mentioning
confidence: 99%